2004
DOI: 10.1136/jnnp.2003.019075
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia in acute stroke patients fed by nasogastric tube

Abstract: Background: Aspiration pneumonia is the most important acute complication of stroke related dysphagia. Tube feeding is usually recommended as an effective and safe way to supply nutrition in dysphagic stroke patients. Objective: To estimate the frequency of pneumonia in acute stroke patients fed by nasogastric tube, to determine risk factors for this complication, and to examine whether the occurrence of pneumonia is related to outcome. Methods: Over an 18 month period a prospective study was done on 100 conse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
156
1
13

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(180 citation statements)
references
References 41 publications
10
156
1
13
Order By: Relevance
“…It was observed that a significant increase in the activation of the sensorimotor cortex occurs on the left compared to the right during swallowing (8) . However, most studies report that patients with lesions in the right hemisphere have more swallowing dysfunction (44) .…”
Section: Discussionmentioning
confidence: 94%
“…It was observed that a significant increase in the activation of the sensorimotor cortex occurs on the left compared to the right during swallowing (8) . However, most studies report that patients with lesions in the right hemisphere have more swallowing dysfunction (44) .…”
Section: Discussionmentioning
confidence: 94%
“…[5] Stroke severity as measured using the National Institute of Health Stroke Scale (NIHSS) score is the only factor associated with pneumonia, [1] and is a predictor of poor outcome. [6] The increasing length of stay (>5 h) at the emergency department was found to worsen the neurologic outcome but not mortality. [7] Pneumonia has been one of the top causes of mortality in acute stroke patients in our institution over the years.…”
Section: Introductionmentioning
confidence: 99%
“…Studies regarding the effects of infection on worsening stroke symptoms have yielded ambiguous results [14]. While several studies could not demonstrate an independent association between infection and worsening of neurological deficit after stroke [15][16][17], the majority of studies showed that infections in hospitalized patients in the acute phase after stroke are associated with a worse functional outcome and increased mortality [6,[18][19][20]. In the largest study, Katzan et al [21] described a 30-day mortality of 27 % after poststroke pneumonia compared with a mortality rate of 4 % in patients without pneumonia.…”
Section: Rationale Behind Prophylactic Antibiotic Therapy In Strokementioning
confidence: 99%